Plasma inflammatory cytokines are associated with cognitive impairment after acute minor ischemic stroke and transient ischemic attack - Zhao, PanPan; Zhao, Meng; Zhang, GuiMei; Zhai, WeiJie; Wang, YongChun; Shen, YanXin; Sun, Li (Frontiers in Immunology, 2025)
BackgroundInflammation plays a complex role in post-stroke cognitive impairment (PSCI). The purpose of our study was to explore the possible relationship between peripheral blood inflammatory biomarkers and PSCI.MethodsThis prospective observational cohort study included patients with mild ischemic stroke and transient ischemic attack (TIA) who were hospitalized at the First Hospital of Jilin University between April 2019 and March 2022. Fasting plasma, collected on the second day after admission, was used to detect 10 inflammatory cytokines by ELISA and multifactorial assay. The Montreal Cognitive Assessment scale score < 22 was used as the diagnostic criterion for PSCI. We explored the associations between baseline plasma cytokines and PSCI at 0–30 months of follow-up using multivariable logistic regression and further applied structural equation modeling (SEM) to explore the potential pathways.ResultsA total of 236 patients were included in the analysis. Interleukin-18 (IL-18), matrix metalloproteinase-9 (MMP-9), and macrophage inflammatory protein-1α (MIP-1α) were independently associated with PSCI at 3–30 months of follow-up, while IL-18, MMP-9, and IL-8 were independently associated with delayed-onset PSCI (>6 months of follow-up). Similar findings were observed in the sensitivity analysis after excluding the patients with ischemic symptoms with an onset of more than 1 week and those with TIA. The associations of IL-18, MMP-9, and MIP-1α with PSCI remained consistent across age and sex subgroups. In delayed-onset PSCI, IL-18, and MMP-9 showed stable associations, while IL-8 mainly affected patients younger than 65 years. Furthermore, SEM suggested that peripheral inflammation involving MMP-9 and IL-18 mediated the development of PSCI.ConclusionsThe plasma inflammatory markers centered on neutrophils—MMP-9 and IL-18—interact with various risk factors (age, gender, DMTS, DWMH, cerebral atrophy) and contribute to the development of PSCI.Clinical Trial Registrationhttps://www.chictr.org.cn/, identifier ChiCTR1900022675.